2001
DOI: 10.1038/sj.cr.7290062
|View full text |Cite
|
Sign up to set email alerts
|

Differential screening and characterization analysis of the egg envelope glycoprotein ZP3 cDNAs between gynogenetic and gonochoristic crucian carp

Abstract: Gynogenetic silver crucian carp, Carassius auratus gibelio, is an intriguing model system. In the present work, a systemic study has been initiated by introducing suppression subtractive hybridization technique into this model system to identify the differentially expressed genes in oocytes between gynogenetic silver crucian carp and its closely related gonochoristic color crucian carp. Five differential cDNA fragments were identified from the preliminary screening, and two of them are ZP3 homologues. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…It has been known that numerous oocyte-specifically expressed genes play key roles in oogenesis, fertilization and early embryonic development. Recently, subtractive hybridization has been widely used to isolate the oocyte-specific genes in vertebrates including fish (Kanamori, 2000;Xie et al, 2001;Fan et al, 2001), amphibian (Vallee et al, 2005) and mammals (Paillisson et al, 2005;Pennetier et al, 2005;Vallee et al, 2005), and some novel oocyte-specific genes have been screened and identified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been known that numerous oocyte-specifically expressed genes play key roles in oogenesis, fertilization and early embryonic development. Recently, subtractive hybridization has been widely used to isolate the oocyte-specific genes in vertebrates including fish (Kanamori, 2000;Xie et al, 2001;Fan et al, 2001), amphibian (Vallee et al, 2005) and mammals (Paillisson et al, 2005;Pennetier et al, 2005;Vallee et al, 2005), and some novel oocyte-specific genes have been screened and identified.…”
Section: Introductionmentioning
confidence: 99%
“…Gibel carp (Carassius auratus gibelio), as a unique gynogenetic fish distributed in China (Jiang et al, 1983;Zhou et al, 2000a,b;Zhou and Gui, 2002), has been used as an intriguing study model for understanding regulatory mechanisms of oocyte maturation, fertilization and early embryogenesis (Fan et al, 2001;Xie et al, 2001Xie et al, , 2003. Some oocyte-specifically expressed genes, such as ZP3 (Fan et al, 2001;Chen et al, 2005), SNX , C-type lectin (Dong et al, 2004), CaOC1q-like factor (Chen and Gui, 2004), and CagSpindlin (Wang et al, 2005), have been identified and characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the molecular mechanisms underlying the reproductive strategies of gibel carp are poorly understood, making this fish a promising study model for developmental biology (Gui 1996;Zhou et al 2000b;Xie et al 2001Xie et al , 2003. It has been proposed that the reproductive modes of this species may subject to some regulatory factors during oocyte maturation and fertilization (Wang et al 2000;Fan et al 2001;Shi et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, artificial propagation experiments, cytological investigation and molecular marker analysis have proved that the gibel carp should have two different reproductive modes, that is, allogynogenetic reproduction and gonochoristic reproduction (Zhou et al, 2000a,b). All these features make the fish a promising study model for evolutionary genetics and developmental biology (Gui, 1996;Zhou et al, 2000b;Fan et al, 2001;Shi et al, 2002;Xie et al, 2001Xie et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%